Perceptions of veterinary extension staff regarding poultry feed and ingredients in selected districts of Uganda: a qualitative study - Kizza, Daniel; Okello, Samuel; Kalule, Dorothy Nampanzira; Winfred, Awino; Azuba, Rose; Nalubwama, Sylvia; Margret, Nabulime; Joshua, Isiko; Immaculate, Nakabugo; Kayemba, Vincent; Tree, Jennifer M. Jabson; Odoi, Agricola (Springer International Publishing, 2024)
Background Feedstuffs and poultry feeds of low quality are major limitations to the growth of the poultry sector. Methods A qualitative study approach using key informant interviews was used to collect information. The thematic analysis method using a prescribed coding frame was used to analyze the data. Three themes emerged from the data: overview and business environment, consequences and propositions, and quality and enforcement. Results The study revealed that poultry feed sub sector is constituted by several players operating at varying scale of business dealing in either imported concentrates, feed stuffs or complete feed. The sector was not well regulated and there was no systematic surveillance done to evaluate the quality of products (feeds and feedstuffs) sold to the farmers. Some regions did not have any feed analytical facilities and therefore farmers mainly depended on subjective judgement using their sense of sight, smell, taste and touch to evaluate the quality of feedstuffs. Regulatory services such as certification of animal feed mills were insufficient not surprising that poultry farmers complained about feedstuff adulteration. The only requirement in place to operate feed and feedstuff business was an annual trade license. The actors/players in poultry feed business operated independently of their formal body or association. Conclusion This study showed that there is legislation gap in the animal feed sector. The players in the sector were at liberty not to follow standards that ensure quality feeds and feedstuffs.